Treatment Of Secondary Oxidation Pond Effluent Using Hollow Fibre Crossflow Microfiltration And Moringa Oleifera Seeds Extract As Coagulant - Wai, Kien Tat (2003)
A secondary oxidation pond effluent was treated using hollow fibre crossflow micro filtration and coagulation process. Preliminary experiments were carried out to find optimum dosage of Moringa oleifera and alum as coagulants. Optimum dosage of Moringa oleifera in treating low turbid (30-70 NTU) and high turbid (70-100 NTU) secondary oxidation pond effluent was 100 mg/L respectively. About 50% turbidity removal was achieved when using 100 mg/L Moringa oleifera. At optimum dosage of 200 mg/L of alum, 97% turbidity removal was achieved for high turbid samples while 93% turbidity removal was achieved for low turbid samples. Both Moringa oleifera and alum were found to be more efficient in treating high turbid samples. However, alum was more effective in removing turbidity in secondary oxidation pond effluent than Moringa oleifera. Using 10,000 mg/L Moringa oleifera as a stock solution was more suitable than using 5,000 mg/L and 20,000 mg/L Moringa oleifera in removing turbidity in kaolin solution. Next, the performance of micro filtration coupled with coagulation using optimum dosage of Moringa oleifera was investigated. Better flux performance and lower rate of fouling were achieved when combining micro filtration with coagulation. Pseudo-state flux at 3 L/m2.hr and constant suction pressure within 0.6 bar were obtained after 300 hours of filtration time. Removal of COD, BOD5, alkalinity, residual turbidity, TSS, VSS, TDS, TS, temperature and pH in filtrate were not influenced by incorporation of coagulation using Moringa oleifera. Filtrate with quality lower than 50 - mg/L COD, 25 mg/L BOD5, 2 mg CaCO3/L alkalinity, 1 NTU turbidity, 1 mg/L TSS and VSS respectively was produced with micro filtration both with and without coagulation.